(untitled) (Journal of the Entomological Research Society, 2021)
In order to evaluate the Bombyliid species diversity in Guilan province, statistical sampling was performed from designated stations in the desired areas. Totally 20 species belonging to 11 genera were collected as below; Callostoma soror Loew, 1873, Conophorus pseudaduncus Paramonov, 1929, Exoprosopa amseli Oldroyd, 1961, Exoprospora dispar Loew, 1869, Exoprosopa efflatounbeyi Paramonov, 1928, Exoprosopa grandis (Wiedemann in Meigen, 1820), Exoprosopa kirgizorum Paramonov, 1928, Exoprosopa pectoralis Loew, 1862, Hemipenthes subvelutinus Zaitzev, 1966, Heteralonia megerlie (Meigen, 1820), Heteralonia suffuse Klug, 1832, Thyridanthrax elegans (Wiedemann in Meigen, 1820), Thyridanthrax griseolus (Klug, 1832), Thyridanthrax punctum (Loew, 1854), Veribubo misellus, Loew 1869, Lomatia belzebul (Fabricius, 1794), Parageron lutescens (Bezzi, 1925), Usia bicolor Macquart, 1855, Phthiria pulicaria (Mikan, 1796) and Phthiria vagans Loew, 1846. Most of the collected species were from the genus Exoprosopa Macquart, 1840 with relative frequency 54.83 %. According to Shanon-winner index 1.97 the highest species diversity was related to the Darestan region.